Developing football expertise: a football-specific research review - Haugaasen, M.; Jordet, G. (International Review of Sport and Exercise Psychology, 2012)
About 265 million people regularly play football, of which only 0.04% play in a professional league. This suggests that reaching expertise specifically in football is difficult and highly competitive. In recent decades, research on the development of football expertise has increased substantially. However, most of these studies have focused on isolated aspects of the developmental process, and consequently there has been a lack of overview of how these different aspects interact to produce football experts. The aim of this study is to review available research on the development of expertise specific for football. The review is limited to papers found in the electronic SportDiscus database. The 2007 Developmental Model of Sport Participation (DMSP) has been used as the conceptual framework. The results highlight the importance of football-specific practice in early developmental phases in becoming an expert in football. It is also proposed that football-specific nuances may need to be applied to the DMSP in order to make the debate of early specialization versus diversification sufficiently valid for this particular context. Consequences for practice engagement and future research are discussed.